The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1155/2017/6506231
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence among Pregnant Mothers in Northwest Ethiopia: Prevalence and Associated Factors

Abstract: Background. Domestic violence against women is a serious public health concern and human rights violation among pregnant mothers because of its negative effect on the life of both the mother and the fetus. Thus, the aim of this study was to assess the prevalence of domestic violence and associated factors among pregnant women. Methods. An institution based quantitative crosssectional study was conducted among 418 women using a systematic random sampling technique. Binary logistic regression analysis and adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 24 publications
13
28
1
Order By: Relevance
“…Those women living in the rural areas were more likely to have intimate partner violence as compared to those living in the urban areas. It is consistent with previous studies [4,[22][23][24][25].This may be attributed that those women from rural areas may not have access to an information related with the issue.…”
Section: Resultssupporting
confidence: 92%
“…Those women living in the rural areas were more likely to have intimate partner violence as compared to those living in the urban areas. It is consistent with previous studies [4,[22][23][24][25].This may be attributed that those women from rural areas may not have access to an information related with the issue.…”
Section: Resultssupporting
confidence: 92%
“…Housemaid who resided in rural areas and whose family resided in rural area were 2 times more likely to experienced violence as compared to who resided urban area. This nding was consistent with a study conducted in western Ethiopia, eastern India, around Gondar, and Gondar town northwest Ethiopia, showed that rural residency were more likely experience domestic violence [9,18,23,25]. Housemaids who previously resided at country side had no information about violence and they couldn't complain to legal bodies.…”
Section: Discussionsupporting
confidence: 88%
“…Housemaid who resided in rural areas was 3 times more likely to experienced sexual violence as compared to who resided urban area. This nding was consistent with a study conducted in Eastern India, Gondar town northwest Ethiopia and around Gondar northwest Ethiopia showed that rural residency were more likely experience violence where compared to urban residence [17][18][19]. Housemaids who came from rural had no information about violence and they couldn't complain to legal bodies.…”
Section: Factors Associated With Housemaid Sexual Violencesupporting
confidence: 89%